Analysis of Double Materiality Application for Sustainability Reports 2023 - Khairunnisa, Rifdah Yuri; Hartanti, Dwi (Jurnal Ilmu Sosial Mamangan, 2025)
Peraturan Otoritas Jasa Keuangan No. 51/POJK.03/2017 requires public companies to publish a Sustainability Report to the Financial Services Authority and public disclosure. The Sustainability Report functions to respond to challenges in fulfilling sustainability strategies, intended to motivate companies to take advantage of opportunities and mitigate risks so that they can meet stakeholder expectations. Materiality has a fundamental role in the development and preparation of Sustainability Reports. Regulations in the European Union have made it mandatory to apply double materiality as an approach to disclosing material topics in sustainability reporting, which is regulated in Directive (EU) 2022/2464. Double materiality is based on identifying material issues from two perspectives: environmental and social materiality (outward impact) and financial materiality (inward impact). This research aims to analyze the initial application of the double materiality approach to the Sustainability Report 2023 of companies listed on the Indonesian Stock Exchange in the energy sector (IDXENERGY) and the basic material sector (IDXBASIC). Researchers conducted content analysis on companies registered on the Indonesian Stock Exchange which are classified in the energy sector and basic material sector based on the Indonesia Stock Exchange Industrial Classification or IDX-IC. The results reveal the voluntary implementation of the double materiality approach in several companies in the energy sector and basic material sector. This research also shows the suitability of the selection of sustainability topics in the report with the GRI Standards for the oil and gas sector (GRI 11), coal sector (GRI 12) and mining sector (GRI 14).